Potential Pharmacological Chaperones for Cystathionine Beta-Synthase-Deficient Homocystinuria - Majtan, Tomas; Pey, Angel L; Gimenez-Mascarell, Paula; Martínez-Cruz, Luis Alfonso; Szabo, Csaba; Kožich, Viktor; Kraus, Jan P (Handbook of experimental pharmacology, 2018)
Classical homocystinuria (HCU) is the most common loss-of-function inborn error of sulfur amino acid metabolism. HCU is caused by a deficiency in enzymatic degradation of homocysteine, a toxic intermediate of methionine transformation to cysteine, chiefly due to missense mutations in the cystathionine beta-synthase (CBS) gene. As with many other inherited disorders, the pathogenic mutations do not target key catalytic residues, but rather introduce structural perturbations leading to an enhanced tendency of the mutant CBS to misfold and either to form nonfunctional aggregates or to undergo proteasome-dependent degradation. Correction of CBS misfolding would represent an alternative therapeutic approach for HCU. In this review, we summarize the complex nature of CBS, its multi-domain architecture, the interplay between the three cofactors required for CBS function [heme, pyridoxal-5'-phosphate (PLP), and S-adenosylmethionine (SAM)], as well as the intricate allosteric regulatory mechanism only recently understood, thanks to advances in CBS crystallography. While roughly half of the patients respond to treatment with a PLP precursor pyridoxine, many studies suggested usefulness of small chemicals, such as chemical and pharmacological chaperones or proteasome inhibitors, rescuing mutant CBS activity in cellular and animal models of HCU. Non-specific chemical chaperones and proteasome inhibitors assist in mutant CBS folding process and/or prevent its rapid degradation, thus resulting in increased steady-state levels of the enzyme and CBS activity. Recent interest in the field and available structural information will hopefully yield CBS-specific compounds, by using high-throughput screening and computational modeling of novel ligands, improving folding, stability, and activity of CBS mutants.
Keywords: High-Throughput Screening Assays; Homocystinuria; homocystinurie; molekulární chaperony; High-throughput screening; cystathionin-beta-synthasa; Enzyme Stability; stabilita enzymů; posttranslační úpravy proteinů; Homocysteine; rychlé screeningové testy; S-adenosylmethionine; Protein Processing, Post-Translational; zvířata; Humans; Protein misfolding; Pyridoxal-5′-phosphate; sbalování proteinů; Cystathionine beta-Synthase; Molecular Chaperones; Protein Folding; Heme; lidé; Animals